Determinants of Pediatric Tuberculosis in DKI Jakarta During The COVID-19 Pandemic - Simanjorang, Chandrayani; Wangsawinangun, Rana Zahra Raniyah; Karima, Ulya Qoulan; Nurcandra, Fajaria (Jurnal Biostatistik, Kependudukan, dan Informatika Kesehatan, 2024)
The COVID-19 pandemic has affected the diagnosis and treatment of pediatric tuberculosis (TB), which can pose a public health burden if not properly treated. This study aims to find out the risk factors for pediatric TB. The design of this study was cross-sectional, using TB surveillance data extracted from maintenance cards of individuals who underwent TB screening in 2020–2022 at health facilities in DKI Jakarta. The independent variables in this study are age, gender, contact history, BCG immunization, and nutritional status. Logistic regression analysis was performed to identify factors associated with childhood TB after bivariate analysis using chi-square to determine the candidates. There were 14.158 patients as the sample, consisting of 5.9% positive TB. Risk factors associated with pediatric TB are aged 0-4 years (POR=0.3.90; 95% CI=3.32-4.58), male (POR=1.71; 95% CI=1.50-1.98), have a history of contact (POR=0.48; 95% CI=0.40-0.60) and do not have a history of contact (POR=0.78; 95% CI=0.64-0.91). Carrying out routine examinations on children in high TB areas, providing accessible health facilities, exceptional care for infected children, supporting vaccination programs, and promoting self-awareness and environmental sanitation can help prevent and control TB in children.